Arquivo e Memória de Negros - Ferreira, Letícia Elaine [UNESP]; Bizello, Maria Leandra [UNESP] (My University, 2010)
This work analizes the documentation produced by the Municipal Council of Black people in Brazil, both as archival documents and as a rescue innitiative of blacks’ memory. For this purpose, we used the interdisciplinary basis of archival science, the concept of social memory and the history of black movements in Brazil. Legal aspects of Black People Council foundation were raised to provide an understanding of the relations it established with the local government and the municipal city hall. The study of Black movements was fundamental to understand the constitution of this archive, which ensures, in some way, the identity and social participation of black people, beyond the reminiscence of past events from the black people’ group experience. Thus we perceive how the black movement becomes official and legal through the documentation associated to local government; and, in the same way, we observe how their official memory is constituted.

En este trabajo se analiza la documentación producida por el Consejo Municipal del Negro en Brasil en cuanto documentación archivística y de rescate de la memoria de los negros. Para ello, se utilizaron como fundamento interdisciplinar la archivología, la memoria y la historia de los movimientos negros en Brasil. Se analizaron los aspectos legales de creación del Consejo del Negro para comprender las relaciones que establece con el gobierno local y el ayun-tamiento. El estudio de los movimientos negros resultó fundamental para comprender la constitución de ese archivo, que garantiza de alguna manera la identidad y la participación social, más allá de rememorar acontecimientos pasados de la experiencia colectiva de los negros. Así se percibe como el movimiento negro se hace oficial y legal a través de la documentación asociada al gobierno local, y se observa como se constituye la memoria oficial del movimiento.
Archive and Memory of the Black People
Archivo y memoria de Negros
Keywords: Arquivologia; Ciência da Informação; Memória; Movimento negro